ANALYSIS OF EDUCATIONAL POLICY AND ITS IMPLEMENTATION ON THE AUTONOMOUS TERRITORY OF THE MORO NATION: CHALLENGES AND TRANSFORMATION - Roni Putra (Edusoshum : Journal of Islamic Education and Social Humanities, 2023)
The Philippine government's education policy has not been able to run as expected because it has been responded to differently by the Muslim community, thus having an impact on the education system in the Philippines. This situation reflects the dynamics of interests in different directions between the government and society. Therefore, this article will identify education policies and their implementation in the Bangsa Moro autonomous region. The purpose of this article is to analyze educational policies for the Muslim community in Moro. This writing uses the literature review method, which tells about reviews, summaries and written thoughts about various library sources. The Philippines began to accommodate madrasa educational institutions in their national education system. The results of the research show that the educational policy that is implemented is based on a combination of knowledge and cultural integration in society. This combination requires educators to present Islamic education that is integrated and close to students' lives.